The association between parameters of physical activity and olfactory function-the importance of frequency and moderate intensity - Khoosheh Namiranian; Alexandre-Charles Gauthier; Jo-Anne Gilbert; Marie-Eve Mathieu; Marie-Eve Mathieu (Frontiers Media S.A., 2024)
IntroductionOverall physical activity (PA) has been linked to decreased olfactory dysfunction and could improve olfactory function. Additionally, decreased olfactory function can contribute to reduced overall PA levels, given its association with neurodegenerative disorders. This study aims to examine the relationship between specific PA parameters (duration, frequency, intensity) and olfactory function in adults.MethodsA total of 3,527 participants from the National Health and Nutrition Examination Survey (NHANES) 2013-2014 underwent assessments for weekly PA duration, frequency, and intensity, alongside a smell test (including odors such as chocolate, strawberry, grape, onion, smoke, natural gas, leather, and soap). Correlation analyses and binary logistic regressions using SPSS were used to evaluate associations.ResultsThe total smell score exhibited small yet significant positive correlations with the duration, frequency, and volume of moderate PA (correlation coefficients ranging between 0.05 and 0.08; all p ≤ 0.05) and frequency of vigorous PA (correlation coefficient of 0.05; p < 0.05). For moderate PA, the duration, frequency, and volume were significantly and positively associated with the ability to correctly detect the smell of grapes while the frequency was significantly and positively associated with the ability to identify smoke and leather odors (odds ratios ranging from 1.01 to 1.07; p < 0.05). For vigorous PA, the frequency of PA was positively associated with the detection of grape smell (odds ratio of 1.05; p < 0.05).ConclusionSome parameters of an active lifestyle are associated with improved odds of accurately identifying odors by up to 7.4%. Moderate PA duration, frequency, and volume were linked to better olfactory scores, while high-intensity PA had limited associations.